Censoring an Iranian love story a novel - Mandanipur, Shahriyar; Khalili, Sara (New York Afred A. Knopf, 2009)
Shahriar Mandanipour, a contemporary and controversial Iranian writer, presents his first novel written in English. Seamlessly entwining two related narratives, Mandanipour unfolds the tale of an Iranian writer attempting to pen a love story set in present-day Iran. Similar to Romeo and Juliet, the writer's two lovers struggle to endure against powerful external forces. Unfortunately, though, the Ministry of Culture and Islamic Guidance furiously attempts to censor the writer's work.
"Translation of previously unpublished Persian novel."--Title page verso.